2021
DOI: 10.1039/d0bm00870b
|View full text |Cite
|
Sign up to set email alerts
|

The lipid platform increases the activity of STING agonists to synergize checkpoint blockade therapy against melanoma

Abstract: Although selective BRAF inhibitors are current frontline therapeutics in BRAF mutated melanoma, their efficacy is limited by drug resistance. Novel strategies with long-lasting anti-tumor effect are urgently sought after. Activation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Therapeutic benefits of targeting STING pathway have been demonstrated in preclinical murine tumor models. [ 6–9 ] Several clinical trials are ongoing to assess the antitumor efficacy of STING agonists in mono‐ or combination therapies. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic benefits of targeting STING pathway have been demonstrated in preclinical murine tumor models. [ 6–9 ] Several clinical trials are ongoing to assess the antitumor efficacy of STING agonists in mono‐ or combination therapies. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic benefits of targeting STING pathway have been demonstrated in preclinical murine tumor models. [6][7][8][9] Several clinical trials are ongoing to assess the antitumor efficacy of STING agonists in mono-or combination therapies. [10] Cyclic dinucleotides (CDNs) are natural STING agonists but the clinical application of CDNs as immunotherapeutics remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…The newly discovered stimulator of interferon genes (STING), a transmembrane complex located in the endoplasmic reticulum, has opened a new avenue for enhancing the functions of APCs. It has demonstrated that STING activation can stimulate the production of type I interferons (IFNs) via interferon regulatory factor 3 (IRF3) and nuclear factor kappa B (NF-κB) signaling pathways, which can induce the activation of APCs. , Activated APCs indirectly enable the activation and expansion of CD8 + T cells through the interaction between CD4 + T cells and APCs, or can directly activate CD8 + T cells. In addition, type I IFNs can act directly on CD4 + T cells and CD8 + T cells to allow clonal expansion. , Multiple studies have reported that intratumoral injection of the STING agonist (cyclic guanosine monophosphate–adenosine monophosphate, cGAMP) was able to reverse tumor immunosuppression and elicit tumor-specific CD8 + T cells. Therefore, the STING agonist-cGAMP is a potential agent for overcoming the poor immunogenicity of tumor cells and enhancing the functions of APCs. , However, cGAMP is a cyclic di-nucleotide linked by two phosphodiester bonds. Similar to other nucleic acids, it is easy to be degraded by extracellular phosphodiesterase and can hardly cross plasma membrane to enter the cytoplasm. Several recently published studies have demonstrated that nanoparticles could improve the in vivo delivery efficiency of cGAMP, ,, but no co-delivery of cGAMP and siRNA into APCs has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with no treatment or treatment with immune-checkpoint inhibitors alone, the co-administration of STING agonists with CTLA4 and PD1 antibodies in a preclinical HPV + oral tumor model displayed the most significant survival advantage ( 106 ). Moreover, in B16F10- and BRAF-mutated murine models, the group treated with cGAMP encapsulated into lipid nanoparticles conjugated with mannose (LP-cGAMP) and anti-programmed death-ligand 1 (PD-L1) exhibited a more long-lasting inhibition of tumor growth and achieved a more prolonged survival than others ( 107 ).…”
Section: Sting Agonists In Cancer Therapymentioning
confidence: 99%